2020
DOI: 10.2147/rrcc.s274942
|View full text |Cite
|
Sign up to set email alerts
|

<p>Incidence and Predictors of Congestive Heart Failure Among Hemodialysis Patients at Felege Hiote Referral Hospital, Northwest Ethiopia, 2020: Retrospective Cohort Study</p>

Abstract: Background: Heart failure is the cumulative and progressive result of conditions that cause structural defects and functional abnormalities in the heart. It is affects at least 26 million people worldwide and is increasing in prevalence especially among hemodialysis patients with severe renal failure. Objective: To assess the incidence and predictors of congestive heart failure among hemodialysis patients at Felege Hiote Referral Hospital, Northwest Ethiopia. Methods: This institutionally based retrospective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Therefore, in this research, XGBoost, an integrated machine learning algorithm, was applied to identify the complex non-linear relationship between HF and clinical variables, as well as to evaluate the importance of the variables to the HF. Although traditional multivariable analysis methods have been applied for the identification of HF in HD patients ( Gedfew et al, 2020 ; Bramania et al, 2021 ), to our knowledge, this was the first machine learning model for the prediction of HF. Our results showed that the performance of the XGBoost model was better than the traditional logistic regression model in prediction of HF.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this research, XGBoost, an integrated machine learning algorithm, was applied to identify the complex non-linear relationship between HF and clinical variables, as well as to evaluate the importance of the variables to the HF. Although traditional multivariable analysis methods have been applied for the identification of HF in HD patients ( Gedfew et al, 2020 ; Bramania et al, 2021 ), to our knowledge, this was the first machine learning model for the prediction of HF. Our results showed that the performance of the XGBoost model was better than the traditional logistic regression model in prediction of HF.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with specific chronic conditions are referred to the hospital's specialty chronic illness clinics for follow-up (18). FHCSH is a tertiary referral and teaching hospital with 400-bed and around 15 adult OPDs that serve over 7 million people in the surrounding area (19). UoGCSH is a tertiary teaching and referral hospital in Northwest Ethiopia that has over 450 inpatient beds and provides referral health services to over 5 million people.…”
Section: Study Area and Study Designmentioning
confidence: 99%